2016
DOI: 10.1002/ejoc.201501576
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Access to Di‐ and Tri­fluoroethylamines for Lead Structure Research

Abstract: Much research effort has been devoted to the synthesis of fluorinated organic compounds in medicinal chemistry programs. For instance, incorporation of fluorine substituents and trifluoromethyl groups has become a widespread lead optimization strategy owing to the often favorable influence of such moieties on affinity and physicochemical properties. However, introduction of fluoroalkyl groups into dedicated positions of pharmacophores is synthetically challenging. In particular, efficient syntheses of di-and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Recently, we reported the usage of shelf-stable trifluoroacetaldehyde-derived hemiaminal ether building blocks to efficiently access functionalized di- and trifluoromethylated N -aryl amine derivatives . In the course of these studies, we also observed formation of unprecedented pentasubstituted 2,3-dihydro-1 H -imidazoles, bearing a CF 3 group at C-2 and an additional fluorine substituent at C-4 (Figure ).…”
mentioning
confidence: 96%
“…Recently, we reported the usage of shelf-stable trifluoroacetaldehyde-derived hemiaminal ether building blocks to efficiently access functionalized di- and trifluoromethylated N -aryl amine derivatives . In the course of these studies, we also observed formation of unprecedented pentasubstituted 2,3-dihydro-1 H -imidazoles, bearing a CF 3 group at C-2 and an additional fluorine substituent at C-4 (Figure ).…”
mentioning
confidence: 96%